Polystichum napoense (Dryopteridaceae), a new cave-dwelling fern species from Guangxi, China - Xiong, Chi; Li, Zheng-Long; Yang, Zi-Meng; Jiang, Ri-Hong; Huang, Ting (Phytotaxa, 2023)
Polystichum napoense, a new cave-dwelling species of Dryopteridaceae from limestone areas of Napo County, Guangxi, China, was described and illustrated in this study. This species is distinguished by the presence of scales on both surfaces of the pinnae, with scales being particularly distinct on the adaxial pinnae. It is the only known species within P. sect. Haplopolystichum that exhibits this characteristic. The new species has only been found in a single population at the type locality, with an estimated 100–150 plants. Based on the IUCN Red List Categories and Criteria (Version 3.1), P. napoense is considered Critically Endangered (CR).